Effect of different solutions on knoop hardness of indirect composite - Santos, Daniela Micheline dos; Massunari, Loiane; Zavanelli, Adriana Cristina; Haddad, Marcela Filié; Moreno, Amália; Vechiato Filho, A.j.; Goiato, Marcelo Coelho [UNESP] (OMICS International, 2014)
Introduction: Indirect dental composites may have adequate clinical performance. However, the literature is scarce regarding indirect composite resins and these solutions should be considered to maintain their properties. The aim of the study was to evaluate the influence of beverages, mouthwashes and bleaching agents on the hardness of indirect composite resins. Methods: Five different brands of indirect composite resins were evaluated: Adoro, Resilab, Cristobal, Sinfony and Epricord. Ten specimens of each brand were immersed in eleven different solutions: four mouthwashes (Listerine, Oral-B, Plax, Periogard), four beverages (coke soft drink, red wine, coffee, orange juice), three dental bleaching agents (16% peroxide of carbamide, 7.5% and 38% peroxide of hydrogen) and artificial saliva (control group). The Knoop hardness was measured before (baseline) and after 12, 24, 36 and 60 hours of immersion in mouthwashes; after 7, 14 and 21 days of immersion in beverages and after 7 and 14 days of immersion in dental bleaching agents. The results were analyzed using 3-way repeated measures ANOVA and Tukey’s test (p<0.05). Results: All resins presented significant decrease on hardness values after immersion process whereas this reduction was higher for Resilab and Sinfony. The latter exhibited the lowest initial values of hardness while Cristobol resin presented the highest hardness values. The mouthwashes promoted a significant decrease in the hardness of specimens.